2011
DOI: 10.1007/978-3-642-25385-0_33
|View full text |Cite
|
Sign up to set email alerts
|

Natural Generalizations of Threshold Secret Sharing

Abstract: Abstract-We present new families of access structures that, similarly to the multilevel and compartmented access structures introduced in previous works, are natural generalizations of threshold secret sharing. Namely, they admit an ideal linear secret sharing schemes over every large enough finite field, they can be described by a small number of parameters, and they have useful properties for the applications of secret sharing. The use of integer polymatroids makes it possible to find many new such families … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…[13] [14] [15] [16] are recent scheme supporting general access structure. Farras et al [17] suggested natural generalizations of threshold secret sharing.…”
Section: Literature Surveymentioning
confidence: 99%
“…[13] [14] [15] [16] are recent scheme supporting general access structure. Farras et al [17] suggested natural generalizations of threshold secret sharing.…”
Section: Literature Surveymentioning
confidence: 99%
“…These techniques provided a characterization of the hierarchical access structures that admit an ideal perfect secret sharing scheme [12]. Other relevant results on secret sharing have been obtained by using matroid theory as, for instance, the ones in [2,9,13,23].…”
Section: Introductionmentioning
confidence: 99%
“…Because of that, the representability of certain classes of matroids is closely connected to the search for efficient constructions of secret sharing schemes for certain classes of access structures. The reader is referred to [13] for more information about secret sharing and its connections to matroid theory.Several constructions of ideal linear secret sharing schemes for families of relatively simple access structures with interesting properties for the applications have been proposed [2,4,8,9,11,15,18,21,22,23]. They are basic and natural generalizations of Shamir's [19] threshold secret sharing scheme.…”
mentioning
confidence: 99%
“…Several constructions of ideal linear secret sharing schemes for families of relatively simple access structures with interesting properties for the applications have been proposed [2,4,8,9,11,15,18,21,22,23]. They are basic and natural generalizations of Shamir's [19] threshold secret sharing scheme.…”
mentioning
confidence: 99%
See 1 more Smart Citation